2021
DOI: 10.1002/adfm.202105002
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Synthetic Hydroxyapatite Scaffold With In Silico Optimized Macrostructure Enhances Bone Formation In Vivo

Abstract: 3D printing technologies are a promising approach to treat intra-oral bone defects, especially those with poor regenerative potential. However, there is a lack of evidence regarding the impact of internal design specifications on the bone regenerative potential. Here, an in silico approach to optimize the internal design of calcium phosphate-based scaffolds for bone regeneration is proposed. Based on an in silico model of neotissue formation, a gyroid 3D-printed scaffold is designed and manufactured using UV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 67 publications
0
45
1
Order By: Relevance
“…The tissueengineered bone was observed to repair in situ mandibular bone defects in dogs, and Zhang et al 160 were able to reduce the compositing time for these scaffolds from 8 days to 2 days without affecting the in vivo osteogenesis. Using an in silico model, the growth of neotissue was simulated by Van Hede et al 161 for various lattice structures of a 3D-printed HAp scaffold; from this, it was optimized that an internal microporous structure with a pore size of 700 μm and a wall thickness of 200 μm showcased enhanced bone neoformation in a calvarial rat model. By taking into account these dimensions, a gyroid 3Dprinted HAp scaffold was designed and fabricated by UV stereolithography.…”
Section: Incorporation Of Antibacterial Agents and Antioxidantsmentioning
confidence: 99%
“…The tissueengineered bone was observed to repair in situ mandibular bone defects in dogs, and Zhang et al 160 were able to reduce the compositing time for these scaffolds from 8 days to 2 days without affecting the in vivo osteogenesis. Using an in silico model, the growth of neotissue was simulated by Van Hede et al 161 for various lattice structures of a 3D-printed HAp scaffold; from this, it was optimized that an internal microporous structure with a pore size of 700 μm and a wall thickness of 200 μm showcased enhanced bone neoformation in a calvarial rat model. By taking into account these dimensions, a gyroid 3Dprinted HAp scaffold was designed and fabricated by UV stereolithography.…”
Section: Incorporation Of Antibacterial Agents and Antioxidantsmentioning
confidence: 99%
“…The raw materials are costly because they depend on high-priced photosensitive materials [15]. Efforts have been made to reduce feedstock [200][201][202][203] Bone repair/tissue engineering Hydroxyapatite [204][205][206][207][208][209][210][211][212][213][214][215][216], TCP [217][218][219][220][221][222][223][224][225][226][227][228], Al 2 O 3 [229], biosilicate [230], baghdadite [231][232][233], wollastonite-diopside [234], Mgsubstituted wollastonite [235,236], hydroxyapatite+TCP [237][238][239][240][241][242], hydroxyapatite+akermanite [243], calcium phosphate+bioglass [54,…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…In vitro assessments of SLA biocompatibility indicate that these scaffolds provide an environment conducive to osteogenic differentiation and proliferation of several different cell types, including human periosteal-derived stem cells [ 77 ], human mesenchymal stem cells [ 78 , 79 , 80 ], and human embryonic stem cells ( Table 1 ) [ 94 ]. In vivo, SLA-generated scaffolds have shown great success in promoting de novo bone formation, angiogenesis, and osseointegration of the scaffold into murine and rabbit calvarial defects [ 78 , 95 , 96 ]. Using a combination of poly(propylene fumarate) and diethyl fumarate (DEF) as starting materials for the SLA scaffold, Lee et al demonstrated that the addition of microspheres containing BMP-2 into the scaffold resulted in effective bone formation in murine calvarial defects [ 97 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%